Pendampingan Literasi Keuangan dalam Pengambilan Keputusan Investasi pada Pekerja Migran Indonesia di Yunani - Dede Nurohman; Eka Nur Rofik; Agus Eko Sujianto; Diana Lutfiana Ulfa; Ahmad Khudhory; Samsul Huda (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The investment problem that often arises in society is the rampant fraud with unrealistic profit promises. This condition causes financial and psychological losses for the community, especially vulnerable groups such as migrant workers. As part of the responsibility of universities in carrying out community service, financial literacy assistance activities are carried out to improve the understanding and skills of Indonesian migrant workers in Greece. The methods used were in the form of pre-test and post-test to measure the level of knowledge, attitude, and behavior of participants before and after mentoring. The results of the activity showed a significant increase in aspects of knowledge, skills, beliefs, as well as attitudes and behaviors related to financial management. Participants feel real benefits in the form of better ability to recognize investment risks, prepare financial planning, and avoid harmful investment practices. This positive impact emphasizes the importance of financial literacy as a provision for migrant workers in facing economic challenges abroad. Therefore, financial literacy assistance activities are expected to be carried out in a sustainable manner, so that migrant workers have stronger financial resilience, are able to manage income wisely, and avoid misleading investment practices.